Bioactive Compounds from Medicinal Plants for Cancer Therapy and Chemoprevention - George, Blassan (Bentham Science Publishers, 2024)
This book aims to fill research gaps in the search for chemotherapeutic and chemopreventive natural compounds. It includes a collection of detailed reviews focusing on bioactive compounds from plant sources that can be beneficial for cancer therapy. Topics covered include the role of antioxidants in cancer therapy, medicinal plants for cancer chemotherapeutics, bioactive compounds from marine plants, and a review of inhibiting nitric oxide reactions for preventing cancer. Chapters are contributed by researchers who have provided detailed lists and descriptions of the relevant plant sources, the compounds and the biochemical reactions. The book includes references for advanced reading. This book is intended as a reference for scholars and healthcare professionals studying natural medicines for cancer prevention and treatment. Readership Scholars in the field of medicinal chemistry, pharmacology and herbal medicine.